2008
DOI: 10.2981/0909-6396(2008)14[331:lgimco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Lactation growth influences mineral composition of first antler in Iberian red deer Cervus elaphus hispanicus

Abstract: Deer antlers are bony fighting structures which are unique in that they are both easily accessible for analysis and that they are grown every year; thus, they make up good models for the study of bones. Previous studies have shown that antler bone composition is related to the external quality (antler size and weight) and the mechanical quality of the antlers, and that it reflects mineral nutrition and early growth. Because one of the main nutritional factors influencing early growth is maternal milk productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Studies on antler show that K indicates physiological stress in this kind of bone, as its content is greater in distal parts of the antler which are grown when body stores of minerals are near depletion [13], [15]. Similarly, another influence of diet upon antler composition (in this case milk production effects on mineral composition of first deer antler), also pointed to a relation between K and nutrition stress: the lower the milk production by the mothers, the greater the K content in first antlers, whereas the opposite was true for antler ash, Ca and P content [52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on antler show that K indicates physiological stress in this kind of bone, as its content is greater in distal parts of the antler which are grown when body stores of minerals are near depletion [13], [15]. Similarly, another influence of diet upon antler composition (in this case milk production effects on mineral composition of first deer antler), also pointed to a relation between K and nutrition stress: the lower the milk production by the mothers, the greater the K content in first antlers, whereas the opposite was true for antler ash, Ca and P content [52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in winter, farmed deer are generally fed concentrated fodder composed of cereal grains, which are rich in Cr, Mn, Cu, Zn, Se, and Mo [ 35 ]. As shown by Gómez et al [ 5 ], one of the main nutritional factors influencing early growth is maternal milk production and composition; since lactation plays an important role in post-weaning growth, antler quality and the quality of other bones are influenced as well. However, the content of all macroelements, including Ca and P, which are highly important for bone formation, was higher in the bone of wild animals, although insignificantly, than in that of farmed animals, and their Ca-to-P ratio was similar in the two groups (1.5–1.6 for the bone marrow, 2.9 for the bones).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of appropriate feeding is especially important in Cervidae calves, whose survival of the first winter depends on proper body weight (Fenessy et al, 1991). Studies have shown that early growth in young animals, especially in males, is highly important, as it determines some antler traits (weight and length) in adult deer and influences future reproductive success (Gómez et al, 2006.…”
Section: Resultsmentioning
confidence: 99%